2021
DOI: 10.1038/s41467-021-23062-7
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical coupling mechanism for activation and inactivation of an HCN channel

Abstract: Pacemaker hyperpolarization-activated cyclic nucleotide-gated (HCN) ion channels exhibit a reversed voltage-dependent gating, activating by membrane hyperpolarization instead of depolarization. Sea urchin HCN (spHCN) channels also undergo inactivation with hyperpolarization which occurs only in the absence of cyclic nucleotide. Here we applied transition metal ion FRET, patch-clamp fluorometry and Rosetta modeling to measure differences in the structural rearrangements between activation and inactivation of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…It has been shown that the intracellular cyclic nucleotide–binding domain (CNBD) [ 78 ] exerts an inhibiting effect on the transmembrane core of the channel. Binding of cyclic nucleotides to the CNBD leads to a conformational change that is propagated through the C-linker and ultimately relieves inhibition of the transmembrane region, thereby facilitating channel opening [ 14 , 60 , 64 , 74 ]. In this way, changes in the intracellular cAMP concentration significantly regulate HCN channel activity within the physiological range of membrane potentials [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the intracellular cyclic nucleotide–binding domain (CNBD) [ 78 ] exerts an inhibiting effect on the transmembrane core of the channel. Binding of cyclic nucleotides to the CNBD leads to a conformational change that is propagated through the C-linker and ultimately relieves inhibition of the transmembrane region, thereby facilitating channel opening [ 14 , 60 , 64 , 74 ]. In this way, changes in the intracellular cAMP concentration significantly regulate HCN channel activity within the physiological range of membrane potentials [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the translation machinery arrives at the TAG stop-codon site, translation continues by including L-Anap and avoiding mRNA chain termination. This strategy has been previously shown to achieve satisfactory incorporation of L-Anap into exogenously expressed recombinant membrane proteins ( Dai et al, 2019 ; Dai et al, 2021 ; Dai and Zagotta, 2017 ). In our experiments, cells grown without applying pANAP plasmid (tRNA/aaRS), but with BACE1-L500TAG cDNA transfected and L-Anap in media were used as negative controls for the FRET experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Using transition metal ion FRET In spHCN channels, Dai and coworkers determined by combining PCF and molecular modeling differences in the structural rearrangements between activated and inactivated channels and discovered that removing cAMP produced a largely rigid-body rotation of the C-linker relative to the transmembrane domain [ 98 ].…”
Section: Methods To Analyze Activation Gating Preceding Pore Openingmentioning
confidence: 99%